Transforming Tourism: Innovative Business Strategies for Thriving in a Dynamic Industry - Wijaya, Anak Agung Gede (YUME : Journal of Management, 2024)
This study explores the innovative business strategies implemented by tourism industry players in Sanur Beach, Denpasar, focusing on their impact on business sustainability and destination competitiveness. A qualitative approach using case studies and in-depth interviews with 10 purposively selected tourism business owners or managers was employed. Data were also collected through direct observations at the tourist destination and document studies from annual or industry reports. The research identifies the use of digital technologies and sustainability practices as two key strategies to enhance tourist experiences and operational efficiency. Findings show that technologies such as mobile apps, AR/VR, and sustainable resource management, along with empowering local communities, can strengthen competitiveness and ensure long-term business sustainability. However, challenges such as limited resources, privacy concerns, and inadequate regulations to support technological development need to be addressed. The study recommends increased investment in efficient, environmentally friendly technologies and collaboration between the public and private sectors. Future research could explore the impact of integrating social innovation and technology in sustainable tourism, particularly in more remote destinations. Keywords: Innovative Strategy, Business Sustainability, Digital Tourism,